MEDICAL TERMINOLOGY AS A MEAN OF PROFESSIONAL MOBILITY FORMATION OF FUTURE DOCTORS-FOREIGNERS UNDER THE CONDITIONS OF EUROPEAN INTEGRATIONAL PROCESSES - Авраменко, Наталя Олександрівна (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2020)
The article substantiates the urgency of mastering the professional medical terminology by future doctors-foreigners for their professional mobility in the context of European integrational processes. The purpose of this article was to prove that medical terminology plays an important role in the professional communication of future foreign physicians, since it serves as a source of obtaining, storing and transmitting scientific information, as well as a means of mastering a specialty, and to find out that mastering medical terminology is a must. linguistic component of the professional training of future medical doctors. The methods of the study prove that the future foreign physicians acquire a certain basic set of knowledge, skills and competences in the chosen specialty, which is possible if they acquire professional terminology. It plays an important role in the professional communication of people, as it is the source of obtaining, storing and transmitting scientific information, as well as a means of mastering a specialty. The comparative analysis of domestic and foreign scientific researches of the content of the terms "term", "terminology", "professional terminology" is carried out. The result of the study is to consider the peculiarities of the professional terminology of the physician, namely to reveal the essence of medical terminology, because it requires the uniqueness of the interpretation of the basic key concepts, fixed in terms. Therefore, Ukraine, together with other countries, is a participant in the program of international integration into the European space. Future doctor -foreigners are also the category of young people who, in entering the preparatory departments of the Higher Education Institute of Ukraine, undergoes a special program for foreigners to study the language and culture of the country and some specialized disciplines. Future doctors-foreigners will have to acquire some basic knowledge, skills and competencies in their chosen profession while studying at the medical IHE. All this is possible unless you have mastered professional terminology. It plays an important role in the professional communication of people, as it is the source of obtaining, storing and transmitting scientific information, as well as a means of mastering a specialty. A system of exercises for the formation of terminological skills of future doctors-foreigners was developed, the content of educational and methodological support was updated, the author’s special course and methodical recommendations were introduced. To effectively prepare of future doctors-foreigners to master professional terminology during classes, a special course "Ukrainian language for future foreign doctors: a practical course in scientific speech" was organized, aimed at comprehensive mastering of professional terminology. This allowed future doctors-foreigners to quickly and effectively master medical vocabulary and professional terminology, given the interdisciplinary integration.